2x+3=-6-3(2x+4)=x=

Simple and best practice solution for 2x+3=-6-3(2x+4)=x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=-6-3(2x+4)=x= equation:



2x+3=-6-3(2x+4)=x=
We move all terms to the left:
2x+3-(-6-3(2x+4))=0
We calculate terms in parentheses: -(-6-3(2x+4)), so:
-6-3(2x+4)
determiningTheFunctionDomain -3(2x+4)-6
We multiply parentheses
-6x-12-6
We add all the numbers together, and all the variables
-6x-18
Back to the equation:
-(-6x-18)
We get rid of parentheses
2x+6x+18+3=0
We add all the numbers together, and all the variables
8x+21=0
We move all terms containing x to the left, all other terms to the right
8x=-21
x=-21/8
x=-2+5/8

See similar equations:

| 4-10x=-166 | | n÷3=13;n=39 | | 6+k=24 | | 4a-24=a | | y=180,000(1+.03)^10 | | -2-j=-20-9j+9j | | 7x=3(x-24)=x= | | 2(3-p)-17=40 | | 2(X-5)=4x+4-(5-X) | | -13z+12=-14z | | x‐7/4=‐2 | | 3(x+5)=18=x= | | X-10x-30=120 | | –8d–18=–3(d+6)–5d | | 6(5x+6)=12(2x+7) | | 3x+1=4x-2.5 | | x={2.605551275,-4.605551275}+35 | | -5+-2x=-15 | | -4+4x=8+8x | | 3x=5(x+2)=x= | | -13.6r-17.25=-10r+19.23+17.88 | | 3x=8.16 | | 5=1/4c | | pX3=54 | | (x+8)+(x+3)+(x+8)=30 | | 2(x-8)=4=x= | | -4d-20=10+2d | | 1/4x=1/8+2x | | 10-4t=-2t-6 | | -13m+1-20=17-11m | | 6x+4=7x-37 | | h=25(3)-5(3)^2 |

Equations solver categories